Enhancing Mathematics Learning by Integrating Growth Mindset Principles in Ninth-Grade Supplementary Materials - Christian Renales Repuya; Jedh Esterninos (Southeast Asian Mathematics Education Journal, 2022)
This paper determined the supplementary materials in ninth-grade mathematics which may be enhanced to integrate growth mindset principles to improve students’ procedural fluency and foster their growth mindset in mathematics. This study employed a descriptive-developmental method by administering a quasi-experimental design and mixed-method research approach to determine the research questions. The respondents in this study were the 60 ninth-grade students at a state secondary high school in the Philippines. The study implemented the validated researcher-made procedural fluency test and growth mindset questionnaire in determining students’ performance in procedural fluency and mindset in mathematics, respectively. Thematic analysis was employed to investigate students’ responses in Focus Group Discussions (FGD), informal interviews and learning journals in scrutinising the learning experiences and mindsets of the students. Findings displayed that the supplementary materials which can be developed in incorporating growth mindset principles were motivational activities, reflection activities, and instructional videos. Utilising the developed supplementary materials elevates students’ procedural fluency. It influences students to shift from fixed mindsets to growth mindsets in mathematics by providing them with significant learning experiences that help students enhance a growth mindset. Furthermore, the implementation group performed better than the comparison group, particularly with developing growth mindsets. The study results are limited to the participants encompassing; similar research employing the developed supplementary materials to other learning areas with a larger sample is recommended for more generalisable results.